Process integration and intensification : saving energy, water and resources - Klemeš, Jiří Jaromír; Varbanov, Petar Saebev; Alwi, Sharifah Rafidah Wan; Manan, Zainuddin Abdul (De Gruyter graduate., 2014)
Process Integration and Intensification (PII) is one of the most timely topics in chemical and process engineering leading to energy efficient, substantially smaller, cleaner, safer and optimized processes. The book covers optimization fundamentals and industrial applications. It is an authoritative overview meant to help graduate students as well as professionals to effectively apply PII in plant design and operation.